2018
DOI: 10.1002/jbmr.3572
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tissue Mineral Deposition in Response to a Phosphate Pulse in Experimental CKD

Abstract: Pathogenic accumulation of calcium (Ca) and phosphate (PO ) in vasculature is a sentinel of advancing cardiovascular disease in chronic kidney disease (CKD). This study sought to characterize acute distribution patterns of radiolabeled PO and Ca in cardiovascular tissues of rats with CKD (0.25% dietary adenine). The disposition of PO and Ca was assessed in blood and 36 tissues after a 10-minute intravenous infusion of one of the following: (i) PO pulse + tracer PO ; (ii) PO pulse + tracer Ca; or (iii) saline +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The major findings were that (i) renal impairment did not markedly alter normal daily variations in circulating minerals or hormonal regulators in low-normal dietary phosphate conditions, (ii) that the generation of severe hyperphosphatemia in CKD was associated with an attenuated diurnal variation in phosphate and PTH, (iii) the development of VC in CKD was predicted by an early increase in the circulating level of FGF-23, but not PTH or hyperphosphatemia, and (iv) the presence of VC associated with an altered diurnal variation in circulating phosphate. Consistent with previous studies the use of the dietary adenine-induction model of CKD resulted in the progressive development of renal dysfunction with corresponding elevations to circulating creatinine, phosphate, calcium, and FGF-23 (McCabe et al, 2013Shobeiri et al, 2010b;Zelt et al, 2015Zelt et al, , 2019. A high phosphate diet was required to induce severe hyperphosphatemia as well as marked elevation of PTH and FGF-23 in the CKD rats.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The major findings were that (i) renal impairment did not markedly alter normal daily variations in circulating minerals or hormonal regulators in low-normal dietary phosphate conditions, (ii) that the generation of severe hyperphosphatemia in CKD was associated with an attenuated diurnal variation in phosphate and PTH, (iii) the development of VC in CKD was predicted by an early increase in the circulating level of FGF-23, but not PTH or hyperphosphatemia, and (iv) the presence of VC associated with an altered diurnal variation in circulating phosphate. Consistent with previous studies the use of the dietary adenine-induction model of CKD resulted in the progressive development of renal dysfunction with corresponding elevations to circulating creatinine, phosphate, calcium, and FGF-23 (McCabe et al, 2013Shobeiri et al, 2010b;Zelt et al, 2015Zelt et al, , 2019. A high phosphate diet was required to induce severe hyperphosphatemia as well as marked elevation of PTH and FGF-23 in the CKD rats.…”
Section: Discussionsupporting
confidence: 81%
“…Data are represented as Mean ± SD. Diurnal variation was assessed by Cosinor analysis for the clearance of phosphate from the circulation (Zelt et al, 2019). Tissue analysis revealed that in CKD animals with VC a preferential deposition for phosphate into the arteries occurs, contrasting the preference for bone in non-calcified animals, and the kidneys and bone for Controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have extensively characterized the Cy/+ rat as a model of progressive CKD‐MBD, observing biochemical and tissue changes similar to the human disease . Second, the interpretation of absorption using the ligated loop assumes that differences in renal filtration and tissue distribution within the 30 minute timeframe of the test will not significantly affect plasma 33 P. Recently, Zelt and colleagues performed experiments in nephrectomized rats that address these questions. Although kidney filtration was only different between pre‐nephrectomy and post‐nephrectomy beyond a 30‐min period, suggesting that this does not affect our interpretation, the nephrectomized group experienced differences in tissue distribution 30 min post‐i.v.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, this modified adenine‐based dietary protocol caused a slight reduction in bodyweight during the induction of CKD (Table 1). 15,16,26,32 After 4 weeks on the adenine diet, CKD rats were stratified, based on circulating creatinine, into the five calcitriol treatment groups with similar overall severity of CKD: (a) No treatment (0 ng/kg), (b) 5 ng/kg 4 times/day (5D QID, n = 9), (c) 20 ng/kg/ once/day (20D SD, n = 8), (d) 20 ng/kg 4 times/day (20D QID, n = 9), and (d) 80 ng/kg once/day (80D SD, n = 8). Following the sorting of groups according to creatinine, there were no between‐group differences regarding bodyweight, PTH, or FGF‐23.…”
Section: Resultsmentioning
confidence: 99%